Pelaksanaan Pembinaan Usaha Madu Kecamatan Camba Kabupaten Maros - Madiong, Baso; Bahri, Syamsul (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
The Community Partnership Program in Camba District, Maros Regency aims to solve priority problems faced by Honey Farmers, both from the production aspect and the business management aspect. The purpose is to find out and reveal: (1) the development of honey bee production aspects; (2) management of honey farmer group business management. The methods used to produce the output targets to achieve the objectives are: 1) providing assistance to honey farmer business groups in the form of training and socialization; 2) Provide an understanding of the basics of marketing management. The method used is counseling and socialization on how to design product marketing management; 3) provide socialization of effective marketing techniques to consumers. Another priority problem is, honey farmers still use simple production tools, so they do not experience an increase in production yields and do not understand business management and marketing, do not have the right promotion in introducing their products. The output targets to be achieved are divided into 3 aspects, namely production aspects, business management aspects, and business aspects. The output target in the production aspect is that honey farmers can have the ability to increase their production by using processing technology. The output target in the business management aspect is that honey farmers understand marketing management well. As an indicator, the partner group can make a written marketing plan starting from the price of materials, labor costs, selling prices and marketing determination. The output target for the business aspect is that honey farmers already have promotional tools for marketing their products